The use of ratings of perceived exertion for regulating exercise levels in rowing ergometry - Marriott, H. E.; Lamb, K. L. (European Journal of Applied Physiology, 1996)
The purpose of this study was to examine the validity of the use of ratings of perceived exertion (RPE) to estimate and regulate exercise intensity during rowing ergometry. Nine competitive male rowers [mean age 28.6 years, (SD 6.3)] completed two rowing trials on an ergometer. The first trial (estimation) consisted of an incremental protocol designed to elicit a range of work outputs (WO) and heart rates (HR). The subjects indicated their perception of effort using a 15-point scale at each intensity level. In the second trial (production), 7-14 days later, the subjects were asked to produce exercise intensities corresponding to five levels of RPE: 15, 11, 17, 13, and 19. Data analysis revealed high Pearson correlation coefficients between HR and RPE (r = 0.95, P < 0.01) and WO and RPE (r = 0.96, P < 0.01) during the estimation trial. In addition, significant correlations (P < 0.01) were obtained between the estimation and production trials for HR (r = 0.82) and WO (r = 0.84). Posthoc analysis of variance revealed that the observed differences in mean HR were not significant (P > 0.05) at three of the five intensity levels (RPE 15, 17 and 19), but were at the two lowest RPE levels (11 and 13). Significant mean differences in WO were seen at all but RPE 17. These data support the validity of the RPE scale as a measure of physiological strain among competitive male rowers, and offer support for its use as a method of regulating the intensity of rowing ergometry, especially at higher levels.